The quasimonochromatic X-ray radiation source on the basis of the electron beam of the microtron; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 201, Iss. 1 - Adishchev (Adischev) Yu. N. Yuri Nikolaevich; Zabaev V. N. Viktor Nikolaevich; Potylitsyn A. P. Alexander Petrovich; Salikhbaev U. S.; Safarov A. N.; Skripnik B. A.; Stepnov Y. Y.; Khakberdiev I. (1998, 1998)
On the basis of the electron beam (energy E0=13 and 22 MeV) the experimental setup for obtaining of quasimonochromatic X-ray radiation by the method of Bragg diffraction bremsstrahlung X-ray radiation (DXR) has been developed. First results on the obtaining of DXR, confirming the validity of the method, are presented.